2003
DOI: 10.1590/s1516-14392003000200010
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of the 65Zn radiotracer in ZnO polycrystalline ceramics

Abstract: Zinc self-diffusion coefficients were measured in polycrystalline ZnO of high density (>99% of the theoretical density) and of high purity (> 99.999%). The diffusion experiments were performed from 1006 to 1377 °C, in oxygen atmosphere, for times between 16 and 574 h. The diffusion profiles were established by means of Residual Activity Method using the 65Zn radioactive isotope as zinc tracer. In our experimental conditions, the zinc volume diffusion coefficients can be described by the following Arrhenius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
16
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 8 publications
(7 reference statements)
9
16
1
Order By: Relevance
“…The above relation has been derived for (2l/ D pi ) = 0.83, where l is the neck radius and D pi the initial primary-particle diameter, and assumes that the grain-boundary width remains constant during the coalescence process. The literature values of bD GB , [58] g, [59,60] and u are listed in Table 2. To the best of our knowledge, there is only one report on the grain-boundary diffusion coefficients for ZnO.…”
Section: Particle Growth Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…The above relation has been derived for (2l/ D pi ) = 0.83, where l is the neck radius and D pi the initial primary-particle diameter, and assumes that the grain-boundary width remains constant during the coalescence process. The literature values of bD GB , [58] g, [59,60] and u are listed in Table 2. To the best of our knowledge, there is only one report on the grain-boundary diffusion coefficients for ZnO.…”
Section: Particle Growth Investigationmentioning
confidence: 99%
“…To the best of our knowledge, there is only one report on the grain-boundary diffusion coefficients for ZnO. [58] Based on that report, it was possible to calculate t GB values after extrapolating the grain-boundary diffusion coefficient in the studied temperature range. The grainboundary diffusion coefficient of zinc was used for calculation because of the much higher diffusivity value of zinc compared to that of oxygen.…”
Section: Particle Growth Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…At high Zn pressures Hagemark [9] and Tomlins et al [15] found the component vapour pressure p Zn 1/3 relationship, corresponding to a (p O 2 ) -1/6 dependence of the concentration of electrons. Very high Zn diffusivity was revealed and explained by fast-moving Zn interstitials; however, experimental data appear of the controversial role of grain boundaries in the self-diffusion of ZnO components [16,17]. Static vapour photometry is the method that enables us to increase the sensitivity of tensimetric measurements and thereby develop the study of nonstoichiometry.…”
mentioning
confidence: 99%
“…In Zn rich condition interstitial Zn (Zn i ) or O vacancy (V O ) have relatively lower formation energies than other defects [21]. In polycrystalline ceramics in the same experimental conditions, the grainboundary diffusion coefficients of Zn are approximately 4 orders of magnitude greater than the volume diffusion coefficients of Zn in ZnO [22]. The main stable faces of ZnO consist of distinctly different sites with mainly acid or mainly basic or mixed character.…”
mentioning
confidence: 99%